Closed-channel culture system for efficient and reproducible differentiation of human pluripotent stem cells into islet cells - Hirano, Kunio; Konagaya, Shuhei; Turner, Alexander; Noda, Yuichiro; Kitamura, Shigeru; Kotera, Hidetoshi; Iwata, Hiroo (Biochemical and biophysical research communications, 2017)
Human pluripotent stem cells (hPSCs) are thought to be a promising cell-source solution for regenerative medicine due to their indefinite proliferative potential and ability to differentiate to functional somatic cells. However, issues remain with regard to achieving reproducible differentiation of cells with the required functionality for realizing human transplantation therapies and with regard to reducing the potential for bacterial or fungal contamination. To meet these needs, we have developed a closed-channel culture device and corresponding control system. Uniformly-sized spheroidal hPSCs aggregates were formed inside wells within a closed-channel and maintained continuously throughout the culture process. Functional islet-like endocrine cell aggregates were reproducibly induced following a 30-day differentiation protocol. Our system shows an easily scalable, novel method for inducing PSC differentiation with both purity and functionality. •A simple, closed-channel-based, semi-automatic culture system is proposed.•Uniform cell aggregate formation and culture is realized in microwell structure.•Functional islet cells are successfully induced following 30-plus-day protocol.•System requires no daily medium replacement and reduces contamination risk.